Patch clearcutting to regenerate mahogany (Swietenia macrophylla King) and sustain forest value in the Mayan ejidos of Mexico [poster] - Snook, Laura K.; Negreros-Castillo, P. (Center for International Forestry Research, 2002)
To mimic catastrophic disturbances which favor the natural regeneration of mahogany, eight 5000 m2 clearings were established in production forests in Quintana Roo, Mexico using each of three treatments: complete felling; slashing, felling and burning; or machine-clearing, which uprooted all prior vegetation. Twenty mahogany seedlings were planted in the center of each clearing shortly afterwards; and another twenty the next year. Seedlings were also planted both years under the forest canopy. Seedlings on half of the clearings were cleaned at one year and again 7 months later. Fifty-eight months later, only 5% of mahogany seedlings survived under the canopy, as compared to 31% on felled clearings and 48% on burned or machine-made clearings. Average annual growth of seedlings planted the year clearings were opened was higher by 60% (on burned clearings) to 70% (on felled and machine-clearings) than that of seedlings planted a year later, after vegetation had started to regrow. At 58 months, growth was significantly higher on burned clearings, averaging 378 cm and reaching 585 cm among the fastest-growing seedlings, than on felled or machine-made clearings. Surviving seedlings planted under the forest canopy had grown less than 30 cm. On felled clearings, cleaning significantly increased growth to rates similar to those on burned clearings. Effects of cleaning were marginal on burned clearings and not significant on machine-made clearings. The proportion of seedlings attacked by the Hypsipyla grandella shootborer did not vary significantly among treatments, but was affected by cleaning. After 58 months, only 16% of seedlings on uncleaned plots had been attacked, as compared to 49% of seedlings on cleaned plots. The number of shootborer attacks per seedling did vary among treatments, and was highest on burned clearings and lowest on felled clearings, increasing 4-fold on burned clearings and 10-fold on felled and machine-made clearings where seedlings were cleaned. In summary, efforts to regenerate mahogany by enrichment planting under the forest canopy are a waste, but mahogany seedlings survive and grow well on clearings if planted shortly after these are opened. Survival and growth were best on clearings opened by slashing, felling and burning, treatments used by local farmers to create shifting agricultural fields. Cleaning is not necessary or desirable, except on felled clearings, and increases both shootborer attack and vine load. Contrary to widespread assumptions, attack by the shootborer did not represent a constraint to satisfactory rates of survival and growth of mahogany seedlings.